Tinjauan Desain Gapura Jalan di Kota Bandung Menggunakan Metode ATUMICS - Paqih, Rizqi Mohammad; Hanifah, Theasara Ragilia (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2022)
Bandung has many historical relics scattered throughout the city. These historical relics can be in the form of culture, traditions, buildings, and so on. It is undeniable that the gate is a form of sustainable cultural heritage to this day. The unique shape of the gate and its uses can be used as material for analyzing and improvising architectural references in the future. Analysis through the ATUMICS method makes the gate known in terms of its function, form, and aesthetic value. Through this research, things and aesthetic elements of the gate that adorn the main road in the city of Bandung will be explained because apart from being a road decoration, it also has meaning as a marker of a historic city or area. The existence of Jalan L.L.R.E. Martadinata in the city of Bandung has its own uniqueness, the existence of a city gate is an added value to the aesthetic element of the city. It is hoped that this research can provide information related to qualified materials, aesthetic designs, and historical values ​​about the existence of city gates on several streets of Bandung City.